The diversity of the Ukrainian surnames as a tool for population genetic research - Горпинченко, М. Ю.; Атраментова, Л. О. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2014)
The results of the study of Ukrainian surnames for their application ability as quasigenetic markers in population genetic studies have been provided. For this the general set of the names of citizens of Ukraine was taken. The results of the philology research have been compared with the frequency distribution of surnames. The obtained data suggest that the names can serve as a tool for population genetic analysis. Their distribution is not uniform. Also the correlation of the distribution of names with different suffixes with the places of residence has been found.